Leadership Headmaster in Improving the Quality of PAUD in the New Normal Period - Nur Hazizah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Education is the most important thing to maintain/improve its quality and quality. In any condition, institutions and leaders must be able to make decisions and policies to continue to run the education system, such as a pandemic that is sweeping the world, every policy issued by the government must be properly adjusted by the school principal. For this reason, the new normal period must be abolished by the leader in order to be able to implement policies that maintain stability.Keywords: Leadership, Headmaster, Quality, PAUD Institution, New Normal